Die wirtschaftliche Regionalentwicklung zwischen dem Amu-darja-Delta und Westkazachstan unter dem Einfluß des Eisenbahnbaus - Stadelbauer, Jörg (ERDKUNDE, 1974)
The completion of the West-Turanian trunk railway Bejneu-Makat provided a new direct connection between Central Asia and the industrial centre of the Soviet Union. According to its history and function, this railway has its place in the tradition of other Soviet long-distance connections, and it does not cause a fundamental reevaluation of the natural potential in the area between the Aral Sea and the northeastern Caspian Sea. Rather, on account of insufficient watersupply, the natural potential will partly remain unexploited even in the future, although important mineral resources such as mineral oil, natural gas, and non ferrous metal ores have been discovered. A complex development of the region cannot be advanced; however, the railway transports these mineral resources as well as the agricultural products of the Amu-Dar'ya-Delta to the central industrial regions. This new connection is of particular advantage for cotton cultivation which is most important for the self-supporting supply of the Soviet textile industry. Thus, long-distance trade has to be considered a more important consequence than influences upon a region near the railway.